Placental growth factor levels neither reflect severity of portal hypertension nor portal-hypertensive gastropathy in patients with advanced chronic liver disease. Issue 3 (March 2021) - Simbrunner, Benedikt; Stadlmann, Alexander; Schwabl, Philipp; Paternostro, Rafael; Bauer, David J.M.; Bucsics, Theresa; Scheiner, Bernhard; Lampichler, Katharina; Wöran, Katharina; Beer, Andrea; Eigenbauer, Ernst; Pinter, Matthias; et al.
Abstract: Background & Aims: Experimental data indicates that placental growth factor (PLGF) is involved in the pathophysiology of portal hypertension (PH) due to advanced chronic liver disease (ACLD). We investigated serum levels of PLGF and its "scavenger", the receptor soluble fms-like tyrosine kinase-1 (sFLT1, or sVEGFR1), in ACLD patients with different severity of PH and portal-hypertensive gastropathy (PHG). Methods: PLGF and sVEGFR1 were measured in ACLD patients with hepatic venous pressure gradient (HVPG) ≥6 mmHg ( n = 241) and endoscopic evaluation of PHG ( n = 216). Patients with pre-/posthepatic PH, TIPS, liver transplantation and hepatocellular carcinoma were excluded. Results: Thirty-two (13%) patients had HVPG 6–9 mmHg, 128 (53%) 10–19 mmHg and 81 (34%) ≥20 mmHg; 141 (59%) had decompensated ACLD (dACLD). PLGF (median 17.2 vs. 20.8 vs. 22.4 pg/mL; p = 0.002), sVEGFR1 (median 96.0 vs. 104.8 vs. 119.3 pg/mL; p < 0.001) levels increased across HVPG strata, while PLGF/sVEGFR1 ratios remained similar (0.19 vs. 0.20 vs. 0.18 pg/mL; p = 0.140). The correlation between PLGF and HVPG was weak (Rho = 0.190, 95%CI 0.06–0.31; p = 0.003), and the PLGF/sVEGFR1 ratio did not correlate with HVPG ( p = 0.331). The area-under-the-receiver operating characteristics (AUROC) for PLGF to detect clinically significant PH (CSPH;i.e. HVPG ≥ 10 mmHg) yielded only 0.688 (0.60–0.78; p < 0.001). When compared to ACLD patients without PHG, PLGF levels (20 without vs. 21.4 with mild vs. 17.1 pg/mL with severe PHG, respectively; p = 0.005) and PLGF/sVEGFR1 ratios (0.20 vs. 0.19 vs. 0.17; p = 0.076) did not increase with mild and severe PHG. Conclusion: While PLGF levels tended to increase with severity of PH, the PLGF/sVEGFR1 ratio remained stable across HVPG strata. Neither PLGF nor the PLGF/sVEGFR1 ratio had diagnostic value for prediction of CSPH. The severity of PHG was also not associated with stepwise increases in PLGF levels or PLGF/sVEGFR1 ratio.